2014
DOI: 10.1002/app.40530
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxybutyrate and hydroxyvalerate production by Bacillus megaterium strain A1 isolated from hydrocarbon‐contaminated soil

Abstract: In this study, we attempted to find an alternative microbial resource as a bioplastic producer. Among all of the isolates, the A1 strain produced 44% poly(β‐hydroxybutyrate) (PHB) in proportion to its dry cell weight. The molecular identification of the 16S RNA gene showed that this bacterium was a strain of Bacillus megaterium with the accession number KC579390. The optimization studies led us to the conclusion that the highest poly(β‐hydroxybutyrate‐co‐hydroxyvalerate) (PHBV) production was 78% when 5% molas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The optimum temperature for growth and PHBV accumulation was 31 °C, which was the same as observed during the PHB production studies with this bacterium (Pillai et al 2017a). Besides, Masood et al (2012) and Güngörmedi et al (2014) have also observed that optimum temperature for growth as well as PHA accumulation was in a temperature range of 30-35 °C. The optimum pH for the copolymer production was 7 and the obtained yield showed a significant decreasing trend towards either side of the pH value, which is in agreement with the previous reports on PHBV accumulation in Bacillus spp.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The optimum temperature for growth and PHBV accumulation was 31 °C, which was the same as observed during the PHB production studies with this bacterium (Pillai et al 2017a). Besides, Masood et al (2012) and Güngörmedi et al (2014) have also observed that optimum temperature for growth as well as PHA accumulation was in a temperature range of 30-35 °C. The optimum pH for the copolymer production was 7 and the obtained yield showed a significant decreasing trend towards either side of the pH value, which is in agreement with the previous reports on PHBV accumulation in Bacillus spp.…”
Section: Discussionmentioning
confidence: 93%
“…Reports are also available on the accumulation of copolymers of PHB in several Bacillus spp. when culture medium was supplemented with propionic acid (Güngörmedi et al 2014;Moorkoth and Nampoothiri 2016). B. aryabhattai PHB10 is an environmental bacterial strain accumulating high levels of PHB (Pillai et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is similar to the study of the PHB production from Comamonas sp. [68] and B. megaterium A1 [69]. Acidic pH has no to effect on PHB degradation which is known to depolymerize under alkaline pH conditions [70] and sporulation [71].…”
Section: Plos Onementioning
confidence: 98%
“…). The synthesis of P(3HB-co-3HV) copolymer involves the incorporation of 3HV monomer into the 3HB backbone [12,43,44]. Biopol6 is the trade name that has been producing P(3HB-co-3HV) in a large scale for many years which has been the central PHA marketing strategies by Zeneca and Monsanto [45,46].…”
Section: Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) P(3hbco-3hvmentioning
confidence: 99%